PENDAMPINGAN STRATEGI PENGELOLAAN TRANSFORMASI DIGITAL: E-BUSINESS STRATEGY AND IMPLEMENTATION - Sunarjo, Wenti Ayu; Ari Muhardono; Titi Rahayu Prasetiani; Mukhamad Adzhar Sultan (PT. Berkah Digital Teknologi, 2024)
Sumurjomblangbogo Village has now developed rapidly, especially in improving the performance of SMEs. Since the establishment of the Tirta Arum swimming pool tourism, the development of MSMEs, especially in the culinary sector, has had great opportunities to market their products. People in nearby locations take advantage of the existence of tourist attractions to improve the economy by selling culinary products in canteens or kiosks around tourist locations. However, as time goes by, especially the era of digitalization, the work of MSMEs should be obliged to follow developments in digitalization. Through PkM activities carried out by answering partner problems in the fields of management and marketing. PkM activities carried out in the form of digital transformation activities include; e-business training and mentoring, Qris registration as an alternative to cashless payments and product innovation and diversification to manage competitive business management. PkM activities are carried out at the target of productive partners, namely culinary MSMEs which are members of the KUBE developed by BUMDes Sumurjomblangbogo, Kec. Bojong, Kab. Pekalongan. Furthermore, the results of PkM activities are evaluated for providing solutions to partner problems so that partners can apply the results of training and mentoring. Apart from that, activity partners can become independent MSMEs and are also able to empower competitiveness and achieve all businesses. Abstrak Desa Sumurjomblangbogo kini telah berkembang pesat, terlebih pada peningkatan kinerja UKM. Sejak didirikannya wisata kolam renang tirta arum perkembangan UMKM khususnya bidang kuliner memiliki peluang yang besar untuk memasarkan produknya. Masyarakat di lokasi sekitar memanfaatkan keberadaan objek wisata untuk meningkatkan perekonomian dengan menjual produk kuliner mealui kantin atau kios di sekitar lokasi wisata. Namun seiring perkembangan zaman khusunya era digitalisasi maka kiprah UMKM seyogyanya wajib mengikuti perkembangan digitalisasi. Melalui kegiatan PkM yang dilakukan dengan menjawab permasalahan mitra di bidang manajemen dan pemasaran. Kegiatan PkM yang dilakukan berupa kegiatan transformasi digital diantaranya; pelatihan dan pendampingan e-business, pendaftaran Qris sebagai alternatif pembayaran secara cashless dan inovasi dan diversifikasi produk untuk mengelola manajemen bisnis yang berdaya saing. Kegiatan PkM dilakukan pada sasaran mitra produktif yaitu UMKM kuliner yang tergabung pada KUBE yang dikembangkan oleh BUMDes Sumurjomblangbogo, Kec. Bojong, Kab. Pekalongan. Selanjutnya hasil kegiatan PkM dilakukan evaluasi atas pemberian solusi permasalahan mitra sehingga mitra dapat menerapkan hasil pelatihan dan pendampingan selain mitra kegiatan dapat menjadi UMKM mandiri juga mampu berdaya saing dan mencapai keberlanjutan usaha.